A political psychology of the link between populist beliefs and compliance with COVID-19 containment measures - Uluşahin, Yasemin; Mavor, Kenneth; Reicher, Stephen (Frontiers in Political Science, 2024)
This paper addresses the relationship between populist beliefs and compliance with COVID-19 containment measures. We argue that an understanding of this issue depends upon developing a social/political psychology which addresses the impact of social groups and social relations upon behavior. More specifically we propose that populist beliefs are based on the notion that elite authorities are opposed to the people and hence not to be trusted by them which in turn reduces compliance with what they propose. Furthermore, we draw distinctions between different domains of compliance (getting vaccinated, social distancing and complying with “track and trace”) and different forms of authority (politicians and scientists). We argue that, whereas loss of trust in politicians only undermines engagement with forms of compliance which involve direct engagement with political authority (i.e., track and trace) loss of trust in scientists undermines the very belief that there is a pandemic and hence reduces all forms of compliance. We use a survey of 321 English and Welsh respondents to address these arguments. The data provide weak support for the hypothesis that populism has an effect on compliance through trust in politicians but only in the case of participating in track and trace. The data provide stronger support for the hypothesis that populism has an effect on all forms of compliance through trust in scientists, but only when scientists are perceived as part of the elite. Over all these results demonstrate that the ability to understand the complex relationships between populist beliefs and compliance depends on developing a social/political psychology of COVID-19 which is able to explain how human behavior is shaped by social identities and social relationships which, in turn, are shaped by political ideologies.